Maxwell saves the day [videorecording (DVD)] - Blye, Gary; MacNeil, Ken; Shepherd, Laura; Shekter, Mark; Morley, Glenn; Dolgay, Marvin (Collectible classics., 2004)
Maxwell challenges the boastful bunny, Star, for the honor of delivering the Easter eggs to the children of Brightsville, certain that he's the right rabbit for the job. He and Esmeralda begin their "egg-cellent" adventure by trying to solve the riddle that will show them the right path through Wendell's Wood, but they're in for a "hare-owing" experience. The Great Irk, billygoat king, and his sidekick, Sidney, will do anything to stop Maxwell.